Construction universities as strategic actors: Limitations and variations - Richard Whitley (The University of Manchester, Manchester Business School, 2008)
Recent changes in the funding and governance of research universities have attempted to make them more strategically active in contributing to national goals. However, the ability of universities to develop strategic capabilities as cohesive organisations is limited by the inherent uncertainty of research processes and results, and the dominant influence of scientific communities on research priorities and evaluation standards. Insofar as universities are able to exercise discretion over resource allocation and strategic choices, they are therefore more like investment management companies than integrated firms. The extent to which universities do become more similar to such strategic actors depends on The nature and policies of the state, and the organisation of research funding and the national public science system. The effects of recent changes to the governance of universities on their strategic autonomy and capabilities vary considerably between countries and higher education systems.
Keywords: 330; changing governance of universities; strategic actors; state policies; research funding; national public science systems; organisational capabilities; strategic autonomy; Hochschulreform; Hochschulforschung; Forschungsfinanzierung; Organisatorischer Wandel